The Effect of Night Shift Work on Nurses' Fatigue and Work Concentration in the Emergency Department - Sunanto Sunanto; Rahmat Pannyiwi; Rezqiqah Aulia Rahmat (International Journal of Health Sciences, 2025)
Shifts are part of the work scheduling system in 24-hour hospitals, including the Emergency Department (ER). Night shift work can potentially cause physical and mental fatigue and reduce nurses' concentration, which can impact the quality of care and patient safety. This study aims to analyze the effect of night shifts on nurses' fatigue levels and concentration in the ER of X Regional General Hospital. The study used a quantitative correlational design with a cross-sectional approach. A purposive sample of 60 nurses was selected, with at least 6 months of work experience in the ER and willingness to participate in the study. Data were collected using a Modified Variable Response Questionnaire (MOQ) Fatigue Impact Scale (MFIS) to measure fatigue and Work Concentration Scale (WCS) for work concentration. Data analysis used Pearson correlation with a significance level of α = 0.05. The results of the study showed a significant positive relationship between night shift work and nurse fatigue levels (r = 0.68; p < 0.05) and a significant negative relationship between night shift work and work concentration (r = -0.62; p < 0.05). This indicates that the more frequently nurses work night shifts, the higher their fatigue levels and the lower their work concentration. In conclusion, night shifts increase fatigue and decrease concentration among nurses in the emergency department. Equitable shift schedules and fatigue management programs are recommended to maintain nurse performance and service quality.